A Multicultural Community of Practice in Creative Writing - Chrysogonus Siddha Malilang (Educare)
This article shall argue that learning arts (creative writing) and becoming an artist is best understood as a process of immersion. Lave and Wenger’s Community of Practice will be used as a framework along with the concept of nyantrik, an apprenticeship in arts within Javanese culture, which gives a deeper meaning to the process of immersion. This article will also show how such learning processes may be re-shaped and occur across spatial and cultural boundaries, with the help of modern communication platforms. Using a/r/tography as an approach for arts-based inquiries, the article aims to describe the dialogic learning process of becoming a creative writer through immersion into an online multicultural community of practice, Project 366. The study is accomplished through an examination of the interactions, reflections and creative works (poetry) of the participants, as well as how such exchanges also affected the researcher’s own creative process.